Maternal and placental microbiome and immune crosstalk in pregnancies with small-for-gestational-age fetuses – a pilot case-control study - Kosińska-Kaczyńska, Katarzyna; Krawczyk, Dominika; Bednorz, Martyna; Chaberek, Katarzyna; Czapska, Agnieszka; Zgliczyńska, Magdalena; Goryca, Krzysztof; Piątkowska, Magdalena; Bałabas, Aneta; Czarnowski, Paweł; Żeber-Lubecka, Natalia (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPregnancies complicated by fetal growth restriction are associated with specific bacterial abundances and elevation of proinflammatory cytokines. The aim of the study was to simultaneously analyze the relation between the gut and placenta microbiome and cytokine profile in pregnant women with fetuses appropriate (AGA) and small for gestational age (SGA).Material and methodsWomen with singleton pregnancies at or beyond 32 weeks of gestation were recruited. 11 delivered SGA newborns (study group) and 11 AGA newborns (control group). Samples of maternal venous blood, stool and placenta were collected perinatally.ResultsIn SGA group lower Chao index in placental samples collected from maternal side, while higher Chao index in placental samples collected from fetal side were observed. Taxonomic analysis identified four significantly less abundant genera in samples collected from maternal side. No taxa remained significant after correction in samples from fetal side, but several taxa showed trends of differing abundance. Veillonella showed a trend toward higher abundance in stool samples in SGA group, while other taxa were significant only at a lower threshold. Metabolite analysis revealed that hexanoic acid was significantly elevated compound in the stool of women from the SGA group. Proteobacteria unclassified and Halomonadaceae correlated with stool metabolites, while IL-6 and TNF-α correlated with specific bacterial groups.ConclusionsSpecific changes in the gut microbiome and metabolome as well as placenta microbiome of women with SGA have been observed, with additional associations with inflammatory cytokine levels, suggesting a potential role of these factors in SGA development and highlighting the need for further research.